Ferromagnetism in chemically reduced LiNbO3 and LiTaO3 crystals. (14th April 2016) - Yan, Tao; Ye, Ning; Xu, Liuwei; Sang, Yuanhua; Chen, Yanxue; Song, Wei; Long, Xifa; Wang, Jiyang; Liu, Hong
Abstract: The ferromagnetism of bulk LiNbO3 and LiTaO3 at room temperature was investigated for the first time in the present work. The stoichiometric LiNbO3 is non-magnetic, while congruent LiNbO3 and LiTaO3 show very weak ferromagnetism. After chemical reduction in a mixture of zinc and lithium carbonate powders under flowing nitrogen, the ferromagnetic behavior of each sample became clear, with an increased value of magnetization. The saturation magnetization, the magnetic remanence and the coercive field of reduced congruent LiNbO3 are 7.0  ×  10 −3 emu g −1, 0.65  ×  10 −3 emu g −1 and 0.050 kOe, respectively. The ferromagnetism of chemically reduced LiNbO3 and LiTaO3 can be explained by considering the intrinsic Li vacancies, the appearance of Nb 4+ (or Ta 4+ ) on the surface with non-zero net spin and the oxygen vacancies at the surface.